The Mindset, Family Environment, and Social Media on North Sumatra Housewives’ Interest in Entrepreneurship - Normi, Siti; Mohd Noh, Mohd Shahid Bin (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The aims of this research is to investigate the interplay between mindset, family environment, and social media in influencing the interest of North Sumatra housewives in entrepreneurship. The results of this study, based on the partial hypothesis, stated that the housewives' and family environment mindset in entrepreneurship had a positive and significant effect on increasing entrepreneurial motivation, and these two variables affected the entrepreneurial interest of North Sumatra housewives. Simultaneously, the housewives' and family environment mindset in entrepreneurship, as well as the use of social media for business had a positive and significant effect on North Sumatra housewives’ interest in entrepreneurship through the variable of increasing entrepreneurial motivation. In Islamic perspective, the role of housewives, or women who choose to focus on their domestic responsibilities, is highly respected and valued. Islamic places a significant emphasis on the family unit and recognizes the important roles that both men and women play within it. The Imlication of research this research contributes to a more nuanced understanding of the complex dynamics involved in women's entrepreneurship in a specific cultural and regional context.